Etnikum – Hagyomány – Civil társadalom. Vizsgálódás egy regionális alternatíva körül - A. Gergely, András (Tér és Társadalom, 1989)
In his present paper the author examines if there is a search for ethno-regional identity in Hungary – similarly to international tendencies – and in what way the multiplicity of local subcultures present itself in politics. Following a theoretical introduction, the author describes the local society, the system of communal interactions, the tradition consciousness and the processes of organizing public life in Kiskunhalas, a traditional small town of the Alföld (the Great Hungarian Plain). Particular attention is paid to the issues of historical identity and value consciousness. Remodelling economic environment has also remodified historic structures. He also presents the processes in which a traditional group of the local society appears on the scence of local politics and public life. In the new situation it is inevitable to raise the question of how to interpret tradition and modernization.